Nasopharyngectomy via endoscopic assisted Lefort I osteotomy approach for early stage in recurrence nasopharyngeal cancer - Raja Lope Ahmad, Raja Ahmad Al'konee; Wan Leman, Wan Ishlah; Kamarudin, Norie Azilah; Srinovianti , Noerdin (2005)
Surgical salvage for local recurrence in nasopharyngeal cancer has emerged as an important treatment option. The surgical approaches are divided into inferiorly by midline mandibulotomy or median labiomandibular glossotomy, laterally by facial translocation or transpterygoid approach and anteroposteriorly by maxillary swing or maxillectomy approach. To illustrate our surgical approach for nasopharyngectomy in two cases of recurrence nasopharyngeal cancer by means of endoscopic assisted Lefort I osteotomy. Both patient had achieved complete en-bloc resection of the tumor with the margins were free of the cancer. The morbidity of the surgical approach was minimal and the functional recovery after surgery is excellent. This surgical approach is a viable alternative for early stage in recurrence of nasopharyngeal cancer where the morbidity is minimal and excellent recovery.